Chiefs and Principal Men: A Question of Leadership in Treaty Negotiations - Hansen, Lise C. (Anthropologica, 2022)
During the 19th century, treaties were negotiated with Indian people in Canada to extinguish their interests in vast areas of land prior to settlement by non-natives. Government representatives assumed that chiefs and principal men who signed these treaties represented all bands living in treaty areas, and that signers had the authority to negotiate on behalf of their bands. However, ethnohistorical analysis suggests that this assumption was not necessarily valid, and that the concept of leadership in the context of treaty negotiations needs to be re-examined. Circumstances surrounding the Robinson Superior Treaty of 1850 are used to explore this issue.